Knockdown of a Cyclic Nucleotide-Gated Ion Channel Impairs Locomotor Activity and Recovery From Hypoxia in Adult Drosophila melanogaster - Qiu, Shuang; Xiao, Chengfeng; Robertson, R. Meldrum (Frontiers in Physiology, 2022)
Cyclic guanosine monophosphate (cGMP) modulates the speed of recovery from anoxia in adult Drosophila and mediates hypoxia-related behaviors in larvae. Cyclic nucleotide-gated channels (CNG) and cGMP-activated protein kinase (PKG) are two cGMP downstream targets. PKG is involved in behavioral tolerance to hypoxia and anoxia in adults, however little is known about a role for CNG channels. We used a CNGL (CNG-like) mutant with reduced CNGL transcripts to investigate the contribution of CNGL to the hypoxia response. CNGL mutants had reduced locomotion under normoxia. A shorter distance travelled in a standard locomotor assay was due to a slower walking speed and more frequent stops. In control flies, hypoxia immediately reduced locomotion path length per minute. Flies took 30-40 mins in normoxia for > 90% recovery of path length per minute from 15 mins hypoxia. CNGL mutants had impaired recovery from hypoxia; 40 mins for 10% recovery of walking speed. The effects of CNGL mutation on locomotion and recovery from hypoxia were recapitulated by pan-neuronal CNGL knockdown. Genetic manipulation to increase cGMP in the CNGL mutants increased locomotion under normoxia and eliminated the impairment of recovery from hypoxia. We conclude that CNGL channels and cGMP signaling are involved in the control of locomotion and the hypoxic response of adult Drosophila.